New Endovascular Technique to Prevent Distal Embolism for Iliofemoral Occlusive Disease: Reverse Flow Aspiration With Proximal Sheath Blockage. (August 2017) - Soga, Yoshimitsu; Tomoi, Yusuke; Hiramori, Seiichi; Murata, Naotaka; Kobayashi, Yohei; Ichihashi, Kei; Aodo, Kenji
Purpose: To report the safety and efficacy of a new technique to prevent distal embolism during treatment of iliofemoral occlusions: re verse fl ow a spiration with p roximal sheath blockage (ReFLAP).Method: Between October 2013 and December 2014, 90 patients (mean age 74 years; 66 men) were prospectively enrolled in a study to evaluate the ReFLAP technique during treatment of 110 occlusions in the iliac artery (72, 65%) or superficial femoral artery (SFA; 38, 35%). The mean occlusion lengths of iliac and SFA lesions were 79 and 179 mm, respectively. The concept of ReFLAP is to aspirate debris after balloon dilation using reverse flow through collaterals without antegrade flow. The main endpoints were the incidence of distal embolization, amputation, complications, and the ReFLAP capture rate, which was visually estimated during aspiration using 4 prespecified grades (0, none; 1, foamy debris; 2, small particles; 3, massive particles).Results: ReFLAP was successful in 105 (95.4%) of the 110 lesions attempted; the 5 failures were due to severe vessel tortuosity or calcification. The incidences of distal embolization and amputation were both 0. Minor complications unrelated to ReFLAP were observed in 8 patients. The ReFLAP procedure aspirated debris in 57 (54%) of the 105 lesions. Aspirated material, including marked clots (grades 2 and 3), was confirmed in 40 (38%) of the lesions. The distribution of aspiration grades was significantly different between iliac and SFA lesions (p=0.02).Conclusion: Our results suggest that the ReFLAP endovascular technique to prevent distal embolization during iliofemoral occlusive disease treatment is simple, safe, and effective.